The Narrow Tracks of the Portuguese Economy: Labour, Production, Businesses and Markets - Reis, José (2010)
This text starts with the theoretical premise that diversity is an essential feature of the organization of economies, a position that diverges from the globalist views that have predominated in the social sciences. It moves on to analyse the Portuguese economy through one of its central characteristics, the extensive use of the workforce, arguing that the availability of labour has not led to good entrepreneurial organization, since innovation and inclusion are lacking. Labour is, therefore, the basis of growth, though not of fair redistribution. The dilemmas of the Portuguese economy are additionally affected by what occurs in its limited export markets.